Urine in the pleural space – urinothorax causing massive pleural effusion as a rare complication of percutaneous nephrolithotomy - Divya Khanduja; Naveen Pandhi (Indian Journal of Respiratory Care, 2022)
Urinothorax is a rare condition which is defined as collection of urine in the pleural space due to retroperitoneal leakage of urine into the pleural space. It is a rare cause of transudative pleural effusion. It is usually obstructive or traumatic in etiology. It is a rare complication associated with percutaneous nephrolithotomy (PCNL). We report the case of a 29-year-old female who presented with massive pleural effusion that developed in the patient who had undergone PCNL for renal stones. Thoracocentesis was done, and creatinine levels in pleural fluids were measured for diagnosis of urinothorax. For diagnosis, awareness of condition and high degree of clinical suspicion is required. Imaging modality such as computed tomography of the abdomen is useful for allocation of anatomical defect causing retroperitoneal leakage of urine or urinoma. We highlight the importance of early diagnosis of urinothorax for prompt treatment of the underlying condition.